RNA m6A methylation regulates sorafenib resistance in liver cancer through FOXO3‐mediated autophagy. (5th May 2020) - Lin, Ziyou; Niu, Yi; Wan, Arabella; Chen, Dongshi; Liang, Heng; Chen, Xijun; Sun, Lei; Zhan, Siyue; Chen, Liutao; Cheng, Chao; Zhang, Xiaolei; Bu, Xianzhang; et al.
Abstract: N6‐methyladenosine (m 6 A) is an abundant nucleotide modification in mRNA, known to regulate mRNA stability, splicing, and translation, but it is unclear whether it is also has a physiological role in the intratumoral microenvironment and cancer drug resistance. Here, we find that METTL3, a primary m 6 A methyltransferase, is significantly down‐regulated in human sorafenib‐resistant hepatocellular carcinoma (HCC). Depletion of METTL3 under hypoxia promotes sorafenib resistance and expression of angiogenesis genes in cultured HCC cells and activates autophagy‐associated pathways. Mechanistically, we have identified FOXO3 as a key downstream target of METTL3, with m 6 A modification of the FOXO3 mRNA 3′‐untranslated region increasing its stability through a YTHDF1‐dependent mechanism. Analysis of clinical samples furthermore showed that METTL3 and FOXO3 levels are tightly correlated in HCC patients. In mouse xenograft models, METTL3 depletion significantly enhances sorafenib resistance of HCC by abolishing the identified METTL3‐mediated FOXO3 mRNA stabilization, and overexpression of FOXO3 restores m 6 A‐dependent sorafenib sensitivity. Collectively, our work reveals a critical function for METTL3‐mediated m 6 A modification in the hypoxic tumor microenvironment and identifies FOXO3 as an important target of m 6 A modification in the resistance of HCC to sorafenib therapy. Synopsis: METTL3 depletion in the hypoxic tumor microenvironment promotes sorafenib resistance, tumor progression and induction of autophagy. Stabilization of FOXO3 mRNA through METTL3‐mediated m6A modification is critical to prevent induction of autophagy and resistance. METTL3, a primary m 6 A methyltransferase, is downregulated in sorafenib‐resistant hepatocellular carcinoma (HCC). Depletion of METTL3 enhances sorafenib resistance in HCC under intratumoral environment. FOXO3 is a critical target of METTL3 during sorafenib resistance. m6A modification of FOXO3 promotes mRNA stability in an YTHDF1‐dependent manner. Abstract : Stabilization of FOXO3 mRNA by YTHDF1 is impaired in hypoxic sorafenib‐resistant hepatocellular carcinoma due to downregulation of the RNA methyltransferase METLL3.